Condyle tumor excision through pre-auricular access - Gaetti Jardim, Ellen Cristina; Oliveira, Murilo Moura; Masocatto, Danilo Chizzolini; Faverani, Leonardo Perez; Okamoto, Roberta; SHinohara, Elio Hitoshi (ARCHIVES OF HEALTH INVESTIGATION, 2015)
Background: The surgical approach choice for diseases that affect the preauricular region has been subject of much discussion in the literature. Methods: Pre-auricular access, have been used with high success rate and, during surgery history various modifications of this approach were conducted in order to reduce irreversible sequelae. Conclusions: Therefore, this study is of relevance, since guide the surgeons about the care concerning anatomical structures involved in this surgical approach and describe, by means of a clinical case, its advantages and indications. Descriptors: Facial Nerve; Ear Auricle; Temporomandibular Joint.